Hubungan pola asuh orang tua dengan frekuensi Dan intensitas perilaku temper tantrum Pada anak toddler - Fadila - Dinantia; Ganis - Indriati; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research is to determine the relationship between parenting style with frequency and intensity of temper tantrum behavior in toddler’s. The design of this research is analytic with the type of cross sectional studies. The study was conducted on 84 respondents in the West Sidomulyo Urban Village, Tampan Districts, Pekanbaru using cluster sampling. Measuring instrument was used a questionnaire that had been tested for validity and reliability. The analysis was used univariate and bivariate analysis by pearson chi-square test. The results showed that there is a relationship between parenting style with frequency and intensity temper tantrum behavior in toddler’s (p value 0.044). The results of this study recommends that health workers especially nurses should do health education about the child’s development toddler (1-3 year’s), particularly on emotional development, with expectation that the parent can apply appropriate parenting in educating children, so the children can grow as independent and responsible generation. Keywords:  parenting style, temper tantrum, toddler